Microwave-assisted hydrolysis of biomass over activated carbon supported polyoxometalates. Issue 20 (21st February 2017) - Tsubaki, S.; Oono, K.; Onda, A.; Ueda, T.; Mitani, T.; Hiraoka, M.
Abstract : Activated carbon supported polyoxometalates (AC-POMs) were used for acceleration of hydrolysis of biomass under microwave irradiation. Abstract : Activated carbon supported polyoxometalates (AC-POMs) were used for acceleration of hydrolysis of biomass under microwave irradiation. Microwaves exhibited a higher saccharification rate for cellobiose and green seaweed ( Monostroma latissimum ) over AC-POMs than conductive heating by 1.25 to 1.55-fold. The activity of the AC-POMs was positively correlated with the dielectric loss of the catalysts, suggesting that microwave susceptibility of AC-POMs is relevant to the enhancement of catalysis under microwave irradiation.